RETRACTED: Teaching epidemiology in the I.M. Sechenov First MSMU: the past, the present and the future - N. I. Briko (Сеченовский вестник)
RETRACTED ARTICLEThe article describes the historical aspects of the teaching of epidemiology in the I.M. Sechenov First MSMU, summarizes the results of the activities of the department of epidemiology and evidence-based medicine in recent years; outlines prospective activities of the department and presents innovations in teaching epidemiology to students.